1997
DOI: 10.1055/s-0038-1657726
|View full text |Cite
|
Sign up to set email alerts
|

Partial Blockade of Nitric Oxide Synthase Blunts the Exercise-induced Increase of von Willebrand Factor Antigen and of Factor VIII in Man

Abstract: SummaryBackground: Until now the effects of β-adrenergic agonists have largely been ascribed to their ability to induce intracellular formation of cyclic adenosine monophosphate. Recently evidence has been accumulating that at least some β1 and β2-adrenoceptor effects may be mediated by nitric oxide (NO). Based on these studies, we hypothesized that the β-adrenoceptor mediated increase of von Willebrand factor and factor VIII-activity (FVIII:C) in plasma during exercise, is caused by an NO-dependent mechanism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 23 publications
0
19
0
2
Order By: Relevance
“…The stimulus responsible for exercise-induced increases in plasma vWF content seems to be mediated by β-adrenergic receptors through a nitric oxide-dependent mechanism, and the hemostasis system could be conditioned by endothelial function. 13 Exercise-dependent effects on the coagulant activity of the FVIII-vWF complex have been studied through distinct protocols with different intensities and durations of exercise tests. Despite variations in the experimental protocols, all studies suggest significant increases of the coagulant activity.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulus responsible for exercise-induced increases in plasma vWF content seems to be mediated by β-adrenergic receptors through a nitric oxide-dependent mechanism, and the hemostasis system could be conditioned by endothelial function. 13 Exercise-dependent effects on the coagulant activity of the FVIII-vWF complex have been studied through distinct protocols with different intensities and durations of exercise tests. Despite variations in the experimental protocols, all studies suggest significant increases of the coagulant activity.…”
Section: Discussionmentioning
confidence: 99%
“…VWF can be produced and released by endothelial cells by a variety of stimuli in vitro and in vivo such as hypoxia, 15 inflammatory cytokines, 16 thrombin, 17 leukocyte elastase, 18 histamine, 4 endotoxin, 19 exercise, 20 adrenaline, 21 and especially vasopressin. 22 Indeed, patients with von Willebrand disease are effectively treated with desmopressin, the synthetic analog of vasopressin, to raise their VWF levels.…”
Section: Plasma and Subendothelial Vwfmentioning
confidence: 99%
“…Also, a recent study showed that anaerobic exercise accelerates blood coagulation and activates blood fibrinolytic activity (Ali and Hanachi, 2011). In this regard, if the stimulus responsible for exercise induced increase in plasma von Willebrand factor (vWF) and coagulation factor VIII (FIII), the content seems to be mediated by b-adrenergic receptors through a nitric oxide-dependent mechanism, where the haemostastic system could be conditioned by endothelial function and be modified during the aging process (Jilma et al, 1997). Also, based on one marathon study, despite increased levels of B-thromboglobulin, platelet aggregation was found to decrease after exercise (Rock et al, 1997).…”
Section: Discussionmentioning
confidence: 99%